TEKNIK KOMUNIKASI DATA PADA AD HOC NETWORK COMMUNICATION - Rahmadya, Budi (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
Ad Hoc Network Communication is mobile networks communications and have a high mobility for each of its nodes. This type of network communications is a temporary networkwith utilizing a WiFi network or Bluethoot as a medium of communications. In the entirenetwork, node moves with a speed varying and unpredictable direction. Packets data delivery from the source node to destination node by using an ad hoc network requires its owntechniques. In this research discussed the existing data communication technique inVehicular Ad Hoc Network (VANETs) Communications with attention: Broadcasting Time, Routing Protocol, Message Dissemination, Delay Tolerant Network Dissemination and / DTN.These techniques can increase the delivery ratio / sending data packets to the destination as well as a smaller delay time. In order to maintain the integrity of the data packets received bythe destination node, the authors have proposed a method of duplicate messages in thisresearch.